A Fluorene based fluorogenic ''Turn-off'' chemosensor for the recognition of Cu2+ and Fe3+: Computational modeling and living-cell application - GÖRGÜLÜ, AHMET ORHAN (My University, 2022)
Background: The traditional methods for the detection and quantification of Cu2+ and Fe3+ heavy metal ions are usually troublesome in terms of high-cost, non-portable, time-consuming, special-ized personnel and complicated tools, so their applications in practical analyses is limited. Therefore, the development of cheap, fast and simple-use techniques/instruments with high sensitivity/selectivity for the detection of heavy metal ions is highly demanded and studied. Methods: In this study, a fluorene-based fluorescent \"turn-off\" sensor, methyl 2-(2-((((9H-fluoren-9-yl)methoxy)carbonyl)amino)-3-phenylpropanamido) acetate (probe FLPG) was synthesized via one-pot reaction and characterized by1 H-NMR,13 C-APT-NMR, HETCOR, ATR-FTIR and elemental analysis in detailed. All emission spectral studies of the probe FLPG have been performed in CH3 CN/HEPES (9/1, v/v, pH=7.4) media at rt. The quantum (Φ) yield of probe FLPG decreased con-siderably in the presence of Cu2+ and Fe3+. The theoretical computation of probe FLPG and its complexes were also performed using density functional theory (DFT). Furthermore, bio-imaging experiments of the probe FLPG was successfully carried out for Cu2+ and Fe3+ monitoring in living-cells. Results: The probe FLPG could sense Cu2+ and Fe3+ with high selectivity and sensitivity, and quantita-tive correlations (R2 >0.9000) between the Cu2+/Fe3+ concentrations (0.0−10.0 equiv). The limits of detection for Cu2+ and Fe3+ were found as 25.07 nM and 37.80 nM, respectively. The fluorescence quenching in the sensor is managed by ligand-to-metal charge transfer (LMCT) mechanism. Job’s plot was used to determine the binding stoichiometry (1:2) of the probe FLPG towards Cu2+ and Fe3+. The binding constants with strongly interacting Cu2+ and Fe3+ were determined as 4.56×108 M-2 and 2.02×1010 M-2, respectively, via the fluorescence titration experiments. The outcomes of the computational study supported the fluorescence data. Moreover, the practical application of the probe FLPG was successfully performed for living cells. Conclusion: This simple chemosensor system offers a highly selective and sensitive sensing platform for the routine detection of Cu2+ and Fe3+, and it keeps away from the usage of costly and sophisti-cated analysis systems.
Keywords: Kimya; Analitik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, ANALİTİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, ANALYTICAL; Fizik Bilimleri; Physical Sciences; Bio-imaging; Copper; DFT; Fluorene; Fluorescence sensor; Iron